Glomus mosseae AND Pseudomonas fluorescens AGAINST SOYBEAN MOSAIC VIRUS UNDER DRIP IRRIGATION SYSTEM - Wuye Ria Andayanie; Praptiningsih Gamawati Adinurani; Martin Lukito (SEAMEO BIOTROP, 2024)
ARTICLE HIGLIGHTS- Glomus mosseae and Pseudomonas fluorescens enhance soybean resistance to SMV.- Ten-day drip irrigation stop at bloom stage boosts seed yield and weight.- Treatment reduces disease severity and increases P. fluorescens population.- Water-saving irrigation method improves soybean performance in dry seasons.- Combining G. mosseae and P. fluorescens increases soybean productivity. ABSTRACTSoybeans [Glycine max (L.) Merr.] require much water, especially in the early stages of growth, flowering, and pod formation and filling. Drought stress on soybeans will increase with global climate change. The research aimed to evaluate the efficacy of Glomus mosseae and Pseudomonas fluorescens in inducing systemic resistance to control Soybean Mosaic Virus (SMV) and the performance of soybean plants with drip irrigation in the dry season. The drip irrigation was stopped for ten days at the beginning of bloom, full bloom, beginning pod, and regular drip irrigation. The application of G. mosseae inoculants used 100 g of sterile compost mixed with 30 spores. The liquid inoculum of P. fluorescens was applied on cotyledonary leaves using the watering method. The plants were inoculated with SMV 6 and 12 days after the P. fluorescens treatment. The symptoms of SMV were recorded two weeks after inoculation, and Indirect ELISA detected the virus. The results showed the combination of G. mosseae and P. fluorescens under drip irrigation stopped at the beginning of bloom for ten days on ELISA absorbance values and disease severity of 0.259 and 3.72 %, respectively. Moreover, this treatment showed the highest values for the 100-seed weight, seed yield, and fresh weight of leaves. The technique of giving water by stopping drip irrigation at the beginning of bloom for ten days will help save water and increase the P. fluorescens population optimally in Alfisols with a pH of between 4.5 and 5.1 with incredibly low fertility. The combination of G. mosseae and P. fluorescens population resulted in a significant increase in the number of G. mosseae’s spores by stopping drip irrigation at the beginning of bloom for ten days.